Perfection of Quality Management of Hotel Services - NIKOLSKAYA, Elena Yurievna; LEPESHKIN, Vyacheslav Anatolievich; KULGACHEV, Ivan Petrovich; MATVEEV, Anton Alexandrovich; LEBEDEVA, Olga Yevgenievna (Journal of Environmental Management and Tourism, 2020)
The article is concerned with the development of approaches aimed at enhancing the quality management of hotel services. It has been proved that quality management implies the availability of relevant management sub-systems in the general management system of a hotel, with a primary purpose of controlling the organization and the provision of services. It has been established that hotel businesses cannot operate efficiently without standardizing customer service. The peculiarity of this process is an individual approach and standard structuring. It has been determined that the attainment of high quality will contribute to making a hotel business competitive and profitable by creating a quality management system that suggests marketing-based efficient business management, the establishment of the relevant corporate culture, the introduction of technical quality of services, the application of standards for functional quality of services, the incoming inspection of product quality.